Blockade of RyRs in the ER Attenuates 6-OHDA-Induced Calcium Overload, Cellular Hypo-Excitability and Apoptosis in Dopaminergic Neurons - Huang, Lu; Xue, Ying; Feng, DaYun; Yang, RuiXin; Nie, Tiejian; Zhu, Gang; Tao, Kai; Gao, GuoDong; Yang, Qian (Frontiers in Cellular Neuroscience, 2017)
Calcium (Ca2+) dyshomeostasis induced by endoplasmic reticulum (ER) stress is an important molecular mechanism of selective dopaminergic (DA) neuron loss in Parkinson’s disease (PD). Inositol 1,4,5-triphosphate receptors (IP3Rs) and ryanodine receptors (RyRs), which are located on the ER surface, are the main endogenous Ca2+ release channels and play crucial roles in regulating Ca2+ homeostasis. However, the roles of these endogenous Ca2+ release channels in PD and their effects on the function and survival of DA neurons remain unknown. In this study, using a 6-hydroxydopamine (6-OHDA)-induced in vitro PD model (SN4741 Cell line), we found that 6-OHDA significantly increased cytoplasmic Ca2+ levels ([Ca2+]i), which was attenuated by pretreatment with 4-PBA (an ER stress inhibitor) or ryanodine (a RyRs blocker). In addition, in acute midbrain slices of male Sprague-Dawley rats, we found that 6-OHDA reduced the spike number and rheobase of DA neurons, which were also reversed by pretreatment with 4-PBA and ryanodine. TUNEL staining and MTT assays also showed that 4-PBA and ryanodine obviously alleviated 6-OHDA-induced cell apoptosis and devitalization. Interestingly, a IP3Rs blocker had little effect on the above 6-OHDA-induced neurotoxicity in DA neurons. In conclusion, our findings provide evidence of the different roles of IP3Rs and RyRs in the regulation of endogenous Ca2+ homeostasis, neuronal excitability and viability in DA neurons, and suggest a potential therapeutic strategy for PD by inhibiting the RyRs Ca2+ channels in the ER.